Daya Tarik Wisata Pura Langgar: Representasi Persaudaraan Hindu-Islam di Bali - Ida Bagus Gede Pujaastawa; I Putu Sudana; Bambang Dharwiyanto Putro (Jurnal Kajian Bali (Journal of Bali Studies), 2019)
This article discusses the existence of the Langgar Temple in Bunutin Village, Bangli, as a tourist attraction as well as a representation of interfaith fraternity, especially Hinduism and Islam. Pura Langgar or known as Pura Penataran Agung Dalem Jawa Bunutin, is a complex of places of worship for Hindus in which there are also places of worship for Muslims in the form of langgar buildings. The existence of Langgar Temple is an interesting phenomenon to be studied, because lately began to get tourist visits, especially Muslim tourists. This is a qualitative descriptive study by collecting data through field observation techniques, interviews, literature studies, and document examinations. This study concludes that the existence of Langgar Temple which reflects the history of acculturation between Hindu and Islamic culture is a cultural heritage that is quite potential to attract tourist. The existence of langgar buildings in the temple complex represents the spirit of Hindu-Islamic brotherhood which is very important in building the spirit of multiculturalism in Indonesia.